2011
DOI: 10.1111/j.1872-034x.2011.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of X‐prolyl aminopeptidase 1 rs17095355 polymorphism with biliary atresia in Thai children

Abstract: The association between XPNPEP1 rs17095355 polymorphism and BA has been demonstrated, particularly with the T allele. We hypothesize that the XPNPEP1 rs17095355 polymorphism confers increased susceptibility to the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…This SNP is located upstream of two genes expressed in the hepatobiliary system, XPNPEP1 , encoding X-Prolyl Aminopeptidase 1, and ADD3 , encoding an F-actin binding protein called adducin 3 (Citterio et al 2003; Ersahin et al 2005). Association with the same SNP was replicated in a Thai cohort ( p < 0.003) of 124 BA cases compared against 114 controls (Kaewkiattiyot et al 2011). Both of these investigations were conducted on Asian subjects and there has been no report of this association in other ethnic groups.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…This SNP is located upstream of two genes expressed in the hepatobiliary system, XPNPEP1 , encoding X-Prolyl Aminopeptidase 1, and ADD3 , encoding an F-actin binding protein called adducin 3 (Citterio et al 2003; Ersahin et al 2005). Association with the same SNP was replicated in a Thai cohort ( p < 0.003) of 124 BA cases compared against 114 controls (Kaewkiattiyot et al 2011). Both of these investigations were conducted on Asian subjects and there has been no report of this association in other ethnic groups.…”
Section: Introductionmentioning
confidence: 80%
“…Two independent studies in Asian patients showed an association of 10q25.1 variants with BA (Garcia-Barcelo et al 2010; Kaewkiattiyot et al 2011). Our investigation of genotyped and imputed SNPs in this region indicates that the association to BA at this locus is also present in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological study was conducted on clinical specimens collected upon conclusion of routine examinations and stored as anonymous. Serum samples were obtained from healthy individuals from two previous studies (influenza and biliary atresia control group) [30,31]. Patient identifiers including personal information (name, address) and hospitalization number were removed from these samples to protect patient confidentiality.…”
Section: Methodsmentioning
confidence: 99%
“…70 This association was replicated in Thai ( n = 124) and US ( n = 171) patient cohorts. 71,72 Although the biological relevance of this SNP is not yet known, the differential hepatic expression of ADD3 in affected livers suggest that SNPs in ADD3 might serve as a susceptibility factor or disease modifier. 72 Further progress in the field will require comprehensive, whole-genome mutation surveys in a patient population that is precisely phenotyped and meets stringent criteria for adequate statistical analyses, followed by proof-of-principle experiments to explore the biological relevance of SNPs.…”
Section: Pathogenic Mechanisms Of Diseasementioning
confidence: 99%